2010
DOI: 10.1007/s00381-010-1156-4
|View full text |Cite
|
Sign up to set email alerts
|

Timing of ventriculoperitoneal shunt insertion following spina bifida closure in Kenya

Abstract: This study indicates that in developing countries, patients with SB who present in a delayed fashion but require shunting and have sterile CSF, should have their shunts inserted 5-10 days after SB closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…However, amidst such evidence, it is important to note that the results of the current study present contrasting views of male predominance in the management. With such distinct evidence, it is essential to highlight that some sub-Saharan African countries like Nigeria and Cameroon have presented results showing male predominance during the management, [15,17] hence the results are in line with such findings. Probably an explanation can be connected to ethno-theories where boys are much more treasured than girls in most societies in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 59%
“…However, amidst such evidence, it is important to note that the results of the current study present contrasting views of male predominance in the management. With such distinct evidence, it is essential to highlight that some sub-Saharan African countries like Nigeria and Cameroon have presented results showing male predominance during the management, [15,17] hence the results are in line with such findings. Probably an explanation can be connected to ethno-theories where boys are much more treasured than girls in most societies in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 59%
“…In studies comparing shunt infection rates for children undergoing MMC repair and shunting for hydrocephalus, placement of a shunt at the time of repair has been associated with a dramatically higher rate of infection when compared to placement 5-10 days later in populations with a high risk of substerile birthing conditions [25]. A study by Pople et al [26] suggested that delay beyond 6 months of life for shunting was associated with a lower shunt infection rate than shunting in infants younger than 6 months (5.6 vs. 15.7%) in a modern Western hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Nongenetic structural defects can occur for several reasons. Hydrocephalus is strongly associated with myelomeningocele, and this defect is caused by a deficiency of folic acid in the maternal diet (15,21). Multivitamin supplements during pregnancy have been shown to reduce the risk of hydrocephalus (11,15).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocephalus is strongly associated with myelomeningocele, and this defect is caused by a deficiency of folic acid in the maternal diet (15,21). Multivitamin supplements during pregnancy have been shown to reduce the risk of hydrocephalus (11,15). Low maternal age has been associated with a higher risk of hydrocephalus, probably because younger mothers are less likely to receive prenatal screening (25).…”
Section: Discussionmentioning
confidence: 99%